Digitalisasi Geospasial Desa Bonto Cinde: Pemetaan Administratif dan Infrastruktur Desa - Rahmatullah Rahmatullah; Muhammad Muhammad; Dhiah Ayu Pitaloka (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The Hasanuddin University Regional Innovation Thematic Community Service Program in Bonto Cinde village, Bissappu subdistrict, Bantaeng district, is one of the activities that must be carried out by Hasanuddin University students as a tangible form of community service in the context of realizing the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education). The KKN activity aims to provide experience and serve as a learning process for students to explore the potential of the village that can be developed by the community. The KKN implementation method at the location consists of survey activities and planning of additional activities apart from the core activities that have been planned. Based on field observations conducted in Bonto Cinde village, Bissappu sub-district, Bantaeng district, this village has considerable potential for agricultural land use. However, uncertainty regarding administrative boundaries between regions and the lack of digital asset inventory often trigger disputes over land use and misdirected development budget allocations. Therefore, this KKN work program focuses on creating administrative and facility maps of Bonto Cinde Village by utilizing field observation data and digital base maps. The results of this activity are expected to serve as supporting documents for the village government in policy-making and planning village development programs based on spatial data.